ActionScript 3.0 bible - Braunstein, Roger, 1981- (Wiley Pub., 2008)
From the Publisher: ActionScript has matured into a full-fledged, object-oriented programming language for creating cutting-edge Web applications, and this comprehensive book is just what you need to succeed. If you want to add interactivity to Flash, build Flex applications, or work with animation- it's all here, and more. Packed with clear instruction, step-by-step tutorials, and advanced techniques, this book is your go-to guide to unlock the power of this amazing language. Learn the basics, apply object-oriented programming, and more.